Contribución de Carlos Alberto Ferreira de Almeida ó conhecimento da cultura castrexa - Calo Lourido, Francisco (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
This paper is an approach to the methodologies followed by Carlos Alberto Ferreira de Almeida in his researches of History of Art, Archeology and Anthropology. It shows his evolution and the essencial contribution that he made to the knowledge of “Cultura Castreja”